The Aroma Composition of Baby Ginger Paocai - Songming Luo; Qiang Li; Anjun Chen; Xingyan Liu; Biao Pu (Journal of Food Quality)
The purpose of this study was to analyze the volatile compounds in baby ginger paocai and the fresh baby ginger and identify the key aroma components that contribute to the flavor of baby ginger paocai. A total of 86 volatile compounds from the two baby ginger samples were quantified; these compounds were extracted by headspace solid-phase microextraction (HS-SPME) and analyzed by gas chromatography–mass spectrometry (GC-MS). The aroma composition of baby ginger paocai was different from that of fresh baby ginger. Baby ginger paocai was characterized by the presence of aroma-active compounds which varied in concentration from 0.03 to 28.14%. Geranyl acetate was the aroma component with the highest relative content in baby ginger paocai. β-myrcene, eucalyptol, trans-β-ocimene, Z-ocimene, linalool, decanal, cis-citral, geraniol, geranyl acetate, curcumene, and β-bisabolene contributed to the overall aroma of the product of baby ginger paocai which had gone through a moderate fermentation process.